2016
DOI: 10.1158/1538-7445.am2016-1009
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1009: Metabolic reprogramming discriminates aggressive vs. slowly growing preneoplastic lesions at early stages of HCC development

Abstract: Introduction and aim: Among the several changes underlying metabolic reprogramming of cancer cells, increased glucose utilization and its uncoupling from oxygen availability is a well-established phenomenon and has been recognized as a hallmark of cancer. To what extent these metabolic changes are important for the progression of slow growing tumors and whether a metabolic rewiring occurs in the very early stages of neoplastic progression represent key questions on the significance of these metabolic alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Second-generation molecules revert TRAP1dependent SDH inhibition. We have previously reported that TRAP1 downregulates the enzymatic activity of SDH in various tumor cell types, 33,36,53,[69][70][71][72] and that this inhibition can be overturned by allosteric TRAP1 inhibition. 33,36,72 We have also shown that SDH inhibition is favored by ERK-dependent TRAP1 phosphorylation in tumor cells endowed with hyperactivation of the Ras/ERK signaling pathway, such as cellular models of malignant peripheral nerve sheath tumors (MPNST), where TRAP1 has been identified as an important determinant of their pro-neoplastic features.…”
Section: Experimental Validation Of the Designs In Biochemical And Ce...mentioning
confidence: 99%
See 1 more Smart Citation
“…Second-generation molecules revert TRAP1dependent SDH inhibition. We have previously reported that TRAP1 downregulates the enzymatic activity of SDH in various tumor cell types, 33,36,53,[69][70][71][72] and that this inhibition can be overturned by allosteric TRAP1 inhibition. 33,36,72 We have also shown that SDH inhibition is favored by ERK-dependent TRAP1 phosphorylation in tumor cells endowed with hyperactivation of the Ras/ERK signaling pathway, such as cellular models of malignant peripheral nerve sheath tumors (MPNST), where TRAP1 has been identified as an important determinant of their pro-neoplastic features.…”
Section: Experimental Validation Of the Designs In Biochemical And Ce...mentioning
confidence: 99%
“…TRAP1 overexpression is associated with several tumor types, including prostate, breast and neurofibromatosis NF1 cancer. [51][52][53] In spite of these observations, induction of TRAP1 levels is somewhat disputed in certain tumor settings, such as kidney cancer. 54,55 These data highlight the complex and only partially understood role of TRAP1 in cancer progression and underline the necessity for specific targeting of its activities.…”
Section: Introductionmentioning
confidence: 99%